Three new species of tiny tarantulas of the genus Thalerommata Ausserer, 1875 (Araneae, Theraphosidae) from northern Colombia - Osorio, Luis M.; Benavides, Léiner; García-Atencia, Sandy; Bertani, Rogério (Zootaxa, 2024)
Thalerommata Ausserer, 1875 is a theraphosid genus with very small species that resemble Trichopelma, although they lack the dot pattern on the abdomen. They are also distinguished from all other Theraphosidae by the presence of flattened, iridescent setae covering the abdomen, and sometimes, the legs too. Its current distribution includes the following countries: Argentina, Bahamas, Colombia, Cuba, Jamaica and Venezuela. Three new species of tiny tarantulas of the genus Thalerommata are described from northern Colombia: Thalerommata yukpa sp. nov. from Cesar Department, Thalerommata kogui sp. nov. and Thalerommata margarita sp. nov. from Magdalena Department. Colombia has now seven of the thirteen Thalerommata species.